PERAN WANITA MUSLIMAH SEBAGAI PENDIDIK DI TENGAH TANTANGAN MODERN - Harun AR., Mariatul Qibtiyah (STAIN Pamekasan, 2010)
Abstract: This paper is trying to capture the role of muslim women. It is like a clock pendulum between the domestic and public sector. In modern times, the roles of women are very different from the previous periods. In the modern era, the roles of women are no longer single but double, which cover the roles in domestic and public sectors as well. In carrying out these double duties, women themselves must improve their multidimensional qualities so that the roles and duties as the first and foremost educators are not crushed and oppressed by the era.